Le bambara écrit à l'école fondamentale (Nordic Journal of African Studies, 2000)
Language competence tests in the 5th grade carried out in Ségou in 1997 show that after four years of Bambara instruction, the children are far from mastering their mother tongue in the written medium. This article analyses 28 stories freely told from a picture, and defines the most frequent types of errors, systemised in three major fields: sentence division, word segmentation and transcription of the sounds that are written differently in Bambara and French. The aim of this analysis is twofold: to help the teachers give more efficient instruction in written Bambara by identifying the most difficult points for the pupils, and to attract the educational authorities’ attention to the fact that if the national languages are not equipped with grammars and orthographic rules, and the teachers are not properly trained to teach them, then mother tongue instruction will not help the children to improve their school results, nor will it develop the national languages as written means of communication.